Religion and violent offenders in boot camp: a structural equation model - Benda, Brent B. (Journal of research in crime and delinquency, 2002)
This is the first study to examine the direct, indirect, and reciprocal relationships between religion and crimes against persons. The study's theoretical model was of males aged 15 to 24 in a boot camp for first admissions to the department of corrections in a southern state. Self-report data indicate that 44 percent of the 600 participants had committed at least five crimes against persons. The hypothesized model represents a theoretical elaboration of social control theory using elements of social learning theories. The pattern of interrelationships comprising the model consists of several reciprocal relationships tested with structural equation modeling procedures. Twenty-seven of the 33 hypothesized relationships are supported. For example, religion is inversely related to carrying a weapon, violence, use of illicit drugs, and selling of illicit drugs. Implications of the study are discussed in terms of measures of religion and the use of religion in formulating explanatory models